Warren Court : A Retrospective - Warren Court : A Retrospective (Oxford Univesity Press, 1996)
A judge-made revolution? The very term seems an oxymoron, yet this is exactly what the Supreme Court under Chief Justice Earl Warren achieved. In Bernard Schwartzs latest work, based on a conference at the University of Tulsa College of Law, we get the first retrospective on the WarrenCourt--a detailed analysis of the Courts accomplishments, including original pieces by well-known judges, professors, lawyers, popular writers such as Anthony Lewis, David Halberstam, David J. Garrow, and a rare personal remembrance by Justice William J. Brennan, Jr.The Warren Court: A Retrospective begins with an examination of the Courts decisions in a variety of different fields, such as equal protection, freedom of speech, freedom of the press, and criminal law. The work continues with The Justices, an intimate look at the principal protagonists in theCourts operation. Then, in A Broader Perspective, the book looks at the Court from an historical perspective, demonstrating its impact on the legal profession and jurisprudence, its international impact, and its legacy.Both readable and informative, The Warren Court: A Retrospective provides an invaluable source for anyone interested in the Court that did so much to change America.